Trends in frequency and causes of uterine rupture in a tertiary care center between year 2001 and 2011 - Zeb, Laila; Bibi, Saeeda (Journal of Postgraduate Medical Institute, 2013)
Objective: To analyze the trends in frequency and causes of uterine rupture between year 2001 and 2011. Methodology: An observational study was done at Lady Reading Hospital Peshawar in year 2011 from 1st January 2011 to 31st December 2011 to analyze the trends in the frequency and causes of ruptured uterusand data was entered in a structured proforma. Same proforma was used to collect data of ruptured uterusin year 2001 from delivery registers, operation room record and patient charts. Results: In year 2011 there were total 5313 deliveries including 1229 caesarean sections. Mean age was35.0+2.0 years. Total 56 cases of ruptured uterus were noted. Frequency of ruptured uterus was 1.05%.Sixty % patients had previous caesarean section. While in year 2001 there ware total 3885 deliveriesincluding 716 caesarean sections. Mean age was 33.0+2.0 years. Total 25 (0.64%) cases of ruptured uteruswere noted. Obstructed labour in grand multigravidas was the commonest cause of ruptured uterus. A3 fold increase in ruptured uterus was seen in association with scarred uterus i.e. in year 2001, 12%patient with ruptured uterus had scarred uterus while in year 2011, 35.7% cases had scarred uterus. Conclusion: Increase trend in frequency of uterine rupture was noted between year 2001 and year 2011.Moreover uterine rupture was more common in scarred uterus following trial of vaginal delivery comparedwith unscarred uterus in year 2011.